Public acceptance of wind energy – concepts, empirical drivers and some open questions - M. Ruddat (Wind Energy Science, 2022)
The further development of wind energy is of major importance for the success of the energy system transformation in Germany and elsewhere. This transition process is not an easy task. For example, the yearly installed capacity of wind energy onshore in Germany has been declining since 2017. Only relatively few new wind turbines were constructed especially in 2019. Problems are, for example, minimum distance requirements (e.g. residential areas, air safety), the high complexity of planning processes and local protests. Social science research has now dealt with the topic of public wind energy acceptance for quite some time. On the one hand, the specific kind of acceptance (e.g. local acceptance) has been subject to scientific discourse. On the other hand, different empirical drivers (e.g. perceived distributional or procedural fairness, trust in relevant actors of the transformation process, risk–benefit perceptions, participation) have been of special interest. This review deals with central definitions and concepts, as well as qualitative and quantitative empirical findings, of social science research concerning the acceptance of wind energy in Germany and elsewhere. Although there has been already a lot of valuable scientific work done, there are still some open questions left.